Synthesis of β-triazolylenones via metal-free desulfonylative alkylation of N-tosyl-1,2,3-triazoles - Pati, Soumyaranjan; Almeida, Renata G.; da Silva Júnior, Eufrânio N.; Namboothiri, Irishi N. N. (Beilstein Journal of Organic Chemistry, 2021)
Desulfonylative alkylation of N-tosyl-1,2,3-triazoles under metal-free conditions leading to β-triazolylenones is reported here. The present study encompasses the synthesis of triazoles with a new substitution pattern in a single step from cyclic 1,3-dicarbonyl compounds and N-tosyl triazole in moderate to high yields. Our synthesis takes place with complete regioselectivity as confirmed by crystallographic analysis which is rationalized by a suitable mechanistic proposal. This method provides an efficient, versatile and straightforward strategy towards the synthesis of new functionalized 1,2,3-triazoles.
Keywords: azoles; cycloaddition; enones; heterocycles; 1,2,3-triazoles

(untitled) - Astruc, D.; Liang, L.; Rapakousiou, A.; Ruiz, J. (Acc. Chem. Res., 2012)

(untitled) - Chu, C.; Liu, R. (Chem. Soc. Rev., 2011)

(untitled) - Finn, M. G.; Fokin, V. V. (Chem. Soc. Rev., 2010)

(untitled) - Lau, Y. H.; Rutledge, P. J.; Watkinson, M.; Todd, M. H. (Chem. Soc. Rev., 2011)

(untitled) - Muller, T.; Bräse, S. (Angew. Chem., Int. Ed., 2011)

(untitled) - Chabre, Y.; Roy, R. (Curr. Top. Med. Chem., 2008)

(untitled) - Colombo, M.; Peretto, I. (Drug Discovery Today, 2008)

(untitled) - Hanselmann, R.; Job, G. E.; Johnson, G.; Lou, R.; Martynow, J. G.; Reeve, M. M. (Org. Process Res. Dev., 2010)

(untitled) - Moumné, R.; Larue, V.; Seijo, B.; Lecourt, T.; Micouin, L.; Tisné, C. (Org. Biomol. Chem., 2010)

(untitled) - Clark, P. R.; Williams, G. D.; Hayes, J. F.; Tomkinson, N. C. O. (Angew. Chem., Int. Ed., 2020)

(untitled) - Chattopadhyay, B.; Gevorgyan, V. (Angew. Chem., Int. Ed., 2012)

(untitled) - Horneff, T.; Chuprakov, S.; Chernyak, N.; Gevorgyan, V.; Fokin, V. V. (J. Am. Chem. Soc., 2008)

(untitled) - Davies, H. M. L.; Alford, J. S. (Chem. Soc. Rev., 2014)

(untitled) - Huisgen, R. (Angew. Chem., Int. Ed. Engl., 1963)

(untitled) - Huisgen, R. (Angew. Chem., Int. Ed. Engl., 1963)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Tornøe, C. W.; Christensen, C.; Meldal, M. (J. Org. Chem., 2002)

(untitled) - Zhang, L.; Chen, X.; Xue, P.; Sun, H. H. Y.; Williams, I. D.; Sharpless, K. B.; Fokin, V. V.; Jia, G. (J. Am. Chem. Soc., 2005)

(untitled) - Johansson, J. R.; Beke-Somfai, T.; Said Stålsmeden, A.; Kann, N. (Chem. Rev., 2016)

(untitled) - Sakai, K.; Hida, N.; Kondo, K. (Bull. Chem. Soc. Jpn., 1986)

(untitled) - Catalán, J.; Sánchez-Cabezudo, M.; De Paz, J. L. G.; Elguero, J.; Taft, R. W.; Anvia, F. (J. Comput. Chem., 1989)

(untitled) - Tomas, F.; Abboud, J. L. M.; Laynez, J.; Notario, R.; Santos, L.; Nilsson, S. O.; Catalan, J.; Claramunt, R. M.; Elguero, J. (J. Am. Chem. Soc., 1989)

(untitled) - Tomas, F.; Catalan, J.; Perez, P.; Elguero, J. (J. Org. Chem., 1994)

(untitled) - Sun, C.; Yuan, X.; Li, Y.; Li, X.; Zhao, Z. (Org. Biomol. Chem., 2017)

(untitled) - Berthold, D.; Breit, B. (Org. Lett., 2018)

(untitled) - Ramachary, D. B.; Reddy, G. S.; Peraka, S.; Gujral, J. (ChemCatChem, 2017)

(untitled) - Wei, H.; Hu, Q.; Ma, Y.; Wei, L.; Liu, J.; Shi, M.; Wang, F. (Asian J. Org. Chem., 2017)

(untitled) - Bhagat, U. K.; Kamaluddin; Peddinti, R. K. (Tetrahedron Lett., 2017)

(untitled) - Bhagat, U. K.; Peddinti, R. K. (J. Org. Chem., 2018)

(untitled) - Roshandel, S.; Lunn, M. J.; Rasul, G.; Muthiah Ravinson, D. S.; Suri, S. C.; Prakash, G. K. S. (Org. Lett., 2019)

(untitled) - Li, Z.; Wei, Q.; Song, L.; Han, W.; Wu, X.; Zhao, Y.; Xia, F.; Liu, S. (Org. Lett., 2019)

(untitled) - Harisha, M. B.; Nagaraj, M.; Muthusubramanian, S.; Bhuvanesh, N. (RSC Adv., 2016)

(untitled) - Gu, C.-X.; Bi, Q.-W.; Gao, C.-K.; Wen, J.; Zhao, Z.-G.; Chen, Z. (Org. Biomol. Chem., 2017)

(untitled) - Bonne, D.; Coquerel, Y.; Constantieux, T.; Rodriguez, J. (Tetrahedron: Asymmetry, 2010)

(untitled) - Rubinov, D. B.; Rubinova, I. L.; Akhrem, A. A. (Chem. Rev., 1999)

(untitled) - Govindh, B.; Diwakar, B. S.; Murthy, Y. L. N. (Org. Commun., 2012)

(untitled) - Ford, A.; Miel, H.; Ring, A.; Slattery, C. N.; Maguire, A. R.; McKervey, M. A. (Chem. Rev., 2015)

(untitled) - Zhang, Y.; Wang, J. (Chem. Commun., 2009)

(untitled) - Baiju, T. V.; Namboothiri, I. N. N. (Chem. Rec., 2017)

(untitled) - Garnovskii, A. D.; Vasil'chenko, I. S. (Russ. Chem. Rev., 2002)

(untitled) - Garnovskii, A. D.; Vasil’chenko, I. S. (Usp. Khim., 2005)

(untitled) - Skopenko, V. V.; Amirkhanov, V. M.; Sliva, T. Y.; Vasil’chenko, I. S.; Anpilova, E. L.; Garnovskij, A. D. (Usp. Khim., 2004)

(untitled) - Aromí, G.; Gamez, P.; Reedijk, J. (Coord. Chem. Rev., 2008)

(untitled) - Lal, S.; Chowdhury, A.; Namboothiri, I. N. N. (Tetrahedron, 2017)

(untitled) - Mane, V.; Kumar, T.; Pradhan, S.; Katiyar, S.; Namboothiri, I. N. N. (RSC Adv., 2015)

(untitled) - Ayyagari, N.; Mehta, A.; Gopi, E.; Deb, I.; Mobin, S. M.; Namboothiri, I. N. N. (Tetrahedron, 2013)

(untitled) - Nair, D. K.; Mobin, S. M.; Namboothiri, I. N. N. (Tetrahedron Lett., 2012)

(untitled) - Ayyagari, N.; Namboothiri, I. N. N. (Tetrahedron: Asymmetry, 2012)

(untitled) - Ayyagari, N.; Jose, D.; Mobin, S. M.; Namboothiri, I. N. N. (Tetrahedron Lett., 2011)

(untitled) - Nair, D. K.; Menna-Barreto, R. F. S.; da Silva Júnior, E. N.; Mobin, S. M.; Namboothiri, I. N. N. (Chem. Commun., 2014)

(untitled) - Kremsmair, A.; Skotnitzki, J.; Knochel, P. (Chem. – Eur. J., 2020)

(untitled) - Jana, K.; Ganguly, B. (ACS Omega, 2018)

(untitled) - Singh, I.; Calvo, C. (Can. J. Chem., 1975)

(untitled) - Hudson, B. S.; Braden, D. A.; Allis, D. G.; Jenkins, T.; Baronov, S.; Middleton, C.; Withnall, R.; Brown, C. M. (J. Phys. Chem. A, 2004)

(untitled) - Ferrari, E.; Saladini, M.; Pignedoli, F.; Spagnolo, F.; Benassi, R. (New J. Chem., 2011)